SUBSTITUSI PUPUK NPK DENGAN BOKASHI ECENG GONDOK (Eichhornia crassipes) PADA PEMBIBITAN TANAMAN LADA - Putri Aulia Rahmah; Gusti Rusmayadi; Hilda Susanti (Universitas Lambung Mangkurat, 2018)
This study aims to obtain the right composition in the use of water hyacinth bokashi that can substitute inorganic fertilizer in pepper plants. This research was carried out using polybag at plantation CV location. Gunung Putri Martapura for 4 months from January to May 2018 with experimental design of Randomized Non-Factorial Complete (RAL) with 5 treatment of plant media composition, namely: p0 = soil + 100% NPK “Mutiara” (without water hyacinth bokashi); p1 = soil: water hyacinth bokashi (3: 1 / v: v) + 75% NPK “Mutiara”; p2 = soil: water hyacinth bokashi (2: 2 / v: v) + 50% NPK “Mutiara”; p3 = soil: water hyacinth bokashi (1: 3 / v: v) + 25% NPK “Mutiara”; p4 = soil: water hyacinth bokashi (1: 3 / v: v) (without NPK “Mutiara”). Each treatment was repeated 4 times so that the entire plot of the experiment was 20 plots. Each plot consists of 5 plants so that there are 100 plants in total. Observations were made on plant height, stem diameter, the number of leaves, length of the segment, sprout age, and dry weight of the plant. Based on the result of the research, the treatment of various plant media composition has no significant effect on plant height, stem base diameter, leaf number, and dry weight of plant, but significantly affect the age of sprout and length of pepper plant so it can be concluded that water hyacinth bokashi in early the growth of pepper plants cannot substitute inorganic fertilizers but can be complimentary of inorganic fertilizers. The best cultivation plant composition treatment on pepper seedling in this study was on soil composition: water hyacinth bokashi (3: 1, v: v) + 75% NPK “Mutiara” and on soil composition: water hyacinth bokashi (2:2; v: v) + 50% NPK “Mutiara”.